An investigation of the challenges of implementing the Risk Based Internal Auditing (RBIA) in the ZNA - Machaya, Vuramayi (Midlands State University, 2017)
The investigation of the challenges of implementing the RBIA in the ZNA was prompted by the growing calls for effective, efficient and economic utilisation of the finite audit resources to achieve the most impact in terms of IA service. The objectives of the study were to identify the key tenets of a RM framework, determine the role of IA within the risk management (RM) framework, determine the adequacy of the RM framework of the ZNA, identify areas of significant risk, and suggest a RM model that is best suited to address the identified risks. The study was conducted in the ZNA King George 6 Barracks. A sample of 43 officers from the departments of Finance, Procurement, IT, Pay, Military Police and IA were chosen as respondents using purposive (judgmental) sampling techniques. Thirty-seven self-administered questionnaires and six personal interviews were used to gather data.